Pulsed Nd :YAG laser micro welding of stainless steel material - Md. Nawi, Ikhwan Naim (2010)
In this study, the influence of various operating parameters of pulsed Nd:YAG laser on the welding of stainless steel material is investigated. The effects of laser peak power, pulse duration, focus point position, number of laser pulse shots and angle of incidence on the weld width and weld penetration depth are analyzed. The laser micro welding is performed using a Unitek Miyachi LW10E ultra compact flash lamp pulsed Nd:YAG laser system with a maximum peak power of 3.5kW. The effects of various pulsed Nd:YAG laser welding parameters on weld pool development are studied by making individual spot welds carefully along the prepared specimens. Then, the weld pool is examined by using a Field Emission Scanning Electron Microscopy (FESEM) to characterize its microstructure. The composition of material before and after welding is analyzed by using an Energy Dispersive X-ray (EDX). The weld width and penetration depth are visualized and captured by using an optical microscope equipped with Charge Couple Devices (CCD) video camera, which is interfaced with image processing system. From the captured image, the Matrox Inspector 2.1 software is used to measure the weld width and weld penetration depth. A laser power of 3.5kW with pulse duration of 2.5kW produces weld width and penetration depth of 0.57mm and 1.31mm, respectively. A mathematical model of penetration depth has been developed. The mathematical model is able to describe the effect of laser beam penetration inside stainless steel material. When the laser beam is incident onto the surface of the material, a fraction of the beam is reflected and the remainder is absorbed into the material. For the time independent laser beam penetration, the power decreases according to the first order of the Bessel function along the radius and drops exponentially with the depth. At a depth of 1.00mm, the power reduces to 0.17kW at the central axis of the weld. The tensile strength of the weld joint is measured using an INSTRON Series IX/s Automated Materials Tester System. The measurement is performed for the butt and lap weld joint with crosshead speed of 0.2mm/min. The tensile strength for single spot butt weld joint is 22.96MPa and 6.90MPa for the lap joint. From the outcome, butt joint provides stronger attachment than the lap joint. In conclusion, pulsed Nd:YAG laser spot micro welding produces good welding on stainless steel and this is a promising technique for miniature assemblies technology such as in photonics packaging.